Analisis Keretanan Website Dengan Aplikasi Owasp Zap - Abdul Fattah Hasibuan; Tommy; Divi Handoko (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Website security is often ignored by developers, including small websites or company profile websites that have data that may be stolen by irresponsible parties. Self-test is needed in order to find out security holes that might be attacked. Therefore, a vulnerability assessment is needed to find security holes. Vulnerability Assessment (VA) is a system scanning process to find vulnerabilities and loopholes in a website system, this loophole provides a backdoor for attackers to attack the victim's system. Owasp-zap is an application that can look for a security hole in the website system, after information about the vulnerability is obtained, the developer can make changes or add scripts to a system so that security holes can be overcome in order to maintain data integrity from attacks by irresponsible parties.